The traction behaviour of high-speed train under low adhesion condition. (January 2022) - Xiao, Guangwen; Wu, Bing; Yao, Linquan; Shen, Quan
Highlights: A three-dimensional train track coupling dynamic model is proposed to simulate the traction behavior. The low adhesion zone between wheel/rail contact are considered. A new anti-slip control algorithm was proposed to ensure the maximum utilization of wheel/rail adhesion. The model is verified by the field data. Abstract: To clarify the train-track traction behaviour in the low adhesion zone, a three-dimensional (3D) train-track coupling dynamic model was developed, in which the train was modelled as a rigid multi-body system with 8 vehicles. The vehicles are connected through coupler devices, which are simplified as nonlinear springs and dampers. The modified FASTSIM algorithm is utilized to obtain the wheel/rail creep force, which can consider the interfacial conditions. A new anti-slip control algorithm was proposed where the traction power could be adjusted to ensure the maximum utilization of wheel/rail adhesion. This control algorithm is achieved by iterating among the traction power, rotational speed and rotational acceleration of each wheelset. Numerical simulation results showed that the traction force would be reduced to a certain level to achieve maximum admissible force when the anti-slip control algorithm is activated. The rotational speed, traction force, creep force, creepages, and coupler force in contaminated conditions were investigated. The results show that the model can effectively simulate the traction process under the low adhesion state, which provides a certain theoretical reference for railway applications.